Perintah Struktural sebagai Upaya Pemulihan Yudisial atas Pelanggaran Hak-Hak Sosial dan Ekonomi: Pembelajaran dari Changing Tides 74 (Pty) Ltd v City of Johannesburg - Lupwana Jean Jacques Kandala; Carlos Joel Tchawouo Mbiada (Badan Strategi Kebijakan Hukum, 2026)
This paper analyses the High Court’s judgment in Changing Tides 74 (Pty) Ltd v City of Johannesburg, a landmark ruling on the intersection of delict law, constitutional rights, and state accountability for failing to comply with a court order to provide alternative accommodation to illegal occupiers. The dispute arose from the City of Johannesburg’s (the City's) failure to comply with a 2012 court order, which compelled the City to provide emergency accommodation to unlawful occupiers prior to their eviction. The failure of the City resulted in the applicant suffering significant economic loss because it had to house the occupiers for three years. The Court found the City liable in delicts for its wrongful and negligent failure to comply with the 2012 court order. The court further found that such conduct infringed both the property rights of the applicant and the right to access to housing of the occupiers. Using a doctrinal legal research method, this research critically assesses the enforceability of structural interdicts, confirms the scope of constitutional delicts, and reemphasises the financial accountability of municipalities that fail to comply with court orders. The research also clarifies the extent of government entities' obligations concerning socioeconomic rights. By awarding over R12 million in damages and punitive costs, the court set a strong precedent for state compliance with socio-economic rights obligations. This paper also considers the broader socio-political implications of the ruling, especially its potential to catalyse reform in municipal governance, human rights enforcement, and intergovernmental relations in service delivery.